Comparative evolution of clinical efficacy of manual tooth brush versus chewable tooth brush a randomized clinical trail - Kola Srikanth Reddy; M Soubhgya; Nuzula Begum; Vikram Vuggirala; K Harshita Nallagula; Nagakishore (Wolters Kluwer Medknow Publications, 2021)
Background: Plaque control is the daily removal of dental plaque, oral biofilms, and also prevention of their accumulation on the other parts of the oral cavity. Dental plaque is the major etiology of maximum gingival and periodontal diseases. This study is an effort to find if chewable brushing is better than manual. Objective: The objective was to evaluate and compare the efficacy of manual toothbrush and chewable toothbrush on fifty patients, in the age group of 8-12 years over a period of 28 days. Materials and Methods: This study used a randomized, double-blinding, single-center, two-treatment, parallel group, design subjects with mild to moderate plaque and gingivitis were evaluated for baseline whole mouth gingival margin and approximal plaque. Clinical assessments were performed using the Quigley-Hein Plaque Index (TQHI) and Simplified Oral Hygiene Index. Subjects received either manual or chewable toothbrush. Data were entered on to the Microsoft Excel and statically analyzed using (SPSS version 21.0 IBM, Chicago III, IL, USA). Data were evaluated by t-test with a P < 0.005 considered to be statistically significant. Results: Fifty subjects participated in the study; 25 in the manual toothbrush and 25 in the chewable toothbrush group. Both brushes demonstrated significant reductions in plaque and gingivitis over the 28 days study period (P < 0.001). The chewable toothbrush was significantly more effective than the manual toothbrush. No adverse events were observed with either brush. Conclusion: The plaque and gingivitis reduction for the chewable toothbrush were significantly greater than for the Manual toothbrush.